Travelling with Darwin and Humboldt. A Transdisciplinary Educational Experience - Martín Ezpeleta, Antonio; Echegoyen-Sanz, Yolanda (Journal of Education Culture and Society, 2019)
Aim. This research aims to confirm that transdisciplinary projects can be very adequate to develop content and competencies traditionally assigned to Sciences and Arts in higher education, exploring the possibilities of outdoor education. Methods. The subjects of the study were one hundred alumni of two different courses “Natural Sciences for Teachers” and “Literary Training for Teachers” at a Spanish university. An educational experience around the phenomenon of scientific travelers was developed, focusing on Charles Darwin and Alexander von Humboldt and the literary genres of travel journals and letters. The main activity contained three phases, including indoor and outdoor education, in which both subjects tackled the same 6 educational topics from a different perspective. After different individual and group activities around those topics, alumni from both subjects merged at a natural environment where a scientific-literary tour took place. At the end of the academic year, an assessment questionnaire with open and closed questions was filled out by all participants. Results and conclusion. After the analysis of all the collected data, we can deduce that the experience was a success. The students appreciated aspects like the setting in which the experience took place, the possibility of interacting with alumni from different courses and the integration of Sciences and Arts. Thus, we have demonstrated that the same activities can be implemented in prototypical subjects of Sciences and Arts and that outdoor education is an ideal resource to achieve a holistic pedagogy engaging the sensory and emotional facets of learning.